Therapeutic effect of camel milk on albino mice (Mus musculus) colon experimentally infected with Entameba histolytica - Rana Hussein Al-Joboury1; Fatima Shihab Al-Nasiri; Ayad Hameed Ebraheem (Tikrit Journal of Pure Science)
The present study aimed to determine the therapeutic effect of camel milk on colonic tissues of albino mice experimentally infected with E. histolytica. Albino mice (Mus musculus) was infected experimentally with E. histolytica cyst stage at a dose 1x106 cell/ml, which was isolated from faecal samples of infected children with E. histolytica who attended to Children's Hospital in the city of Kirkuk at period from May to July 2019. The infected group showed, sever lymphocytes infiltration, and trophozoit stage in the mucous layer with the presence of necrotic materials. In the group of mice which administered with 3 ml of camel milk, colon tissue was normal and there were no histopathological changes compared with mice infected with E. histolytica. While, in the infected group and later treated with camel milk, the histological sections confirm the improvement of colon tissue layers after treatment compared with infected group. Also, in this group, the stages of the parasite were absent. Therefore, from the current study it can be concluded that camel milk has a therapeutic role against the tissue lesions caused by E. histolytica.